Korovkin Type Approximation For Double Sequences Via μ-Statistical A-Summation Process in Modular Spaces - Çınar, Selin; Demirci, Kamil (Sarajevo Journal of Mathematics, 2022)
In the present paper, we extend the Korovkin type approximation theorem via % μ -statistical A-summation process onto the double sequences of positive linear operators in a modular space. We apply our new result to bivariate Mellin-type operators in Orlicz spaces. Then we discuss the reduced results which are obtained by special choices and the matrix sequences.